2017
DOI: 10.1039/c7ra05559e
|View full text |Cite
|
Sign up to set email alerts
|

Matrix composition determines the dimensions of Bacillus subtilis NCIB 3610 biofilm colonies grown on LB agar

Abstract: The production of biomolecules can provide new functionalities to the synthesizing organism. One important example is the secretion of extracellular polymeric substances (EPS) by biofilm forming bacteria. This biofilm matrix protects the individual bacteria within the biofilm from external stressors such as antibiotics, chemicals and shear flow. Previous studies have determined several main matrix components of biofilms formed by Bacillus subtilis. However, how these matrix components influence the growth beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Here, we tested the contribution of this hydrophobin BslA to the surface hydrophobicity of co-cultured colonies by employing a NCIB 3610 mutant strain unable to produce BslA ( ΔBslA ). Indeed, in full agreement with results described in the literature [ 12 , 21 , 22 , [54] , [55] , [56] , [57] , [58] ], co-cultivation of ΔBslA with one of the other strains results in hydrophilic daughter colonies ( Fig. S7 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we tested the contribution of this hydrophobin BslA to the surface hydrophobicity of co-cultured colonies by employing a NCIB 3610 mutant strain unable to produce BslA ( ΔBslA ). Indeed, in full agreement with results described in the literature [ 12 , 21 , 22 , [54] , [55] , [56] , [57] , [58] ], co-cultivation of ΔBslA with one of the other strains results in hydrophilic daughter colonies ( Fig. S7 ).…”
Section: Resultssupporting
confidence: 90%
“…Also, the susceptibility of biofilms towards antibiotic solutions, their resilience to other chemical stresses and the erosion resistance of biofilms were shown to be related to the surface topography of those soft materials [ 9 , 10 ]. In fact, in recent years, quantitative topographical analyses of biofilms have become a well-established and useful tool in biofilm research [ 8 , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,13,14 The exopolysaccharide, whose synthesis is required for the BslA proteins to localize to the biofilm matrix, bundles the cells and contributes—together with BslA—to the final roughness and height of B. subtilis biofilms. 4,15,16 Finally, the fibers formed by TasA protein connect the cells within the matrix, thus rendering the structure of the biofilm more compact and stable. 15,17 Hence, a combination of chemical and physical contributions, that is, hydrophobic molecules and surface roughness features (the latter of which are established by a complex combination of different biofilm matrix components), gives rise to the highly efficient wetting resistance of those biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…4,15,16 Finally, the fibers formed by TasA protein connect the cells within the matrix, thus rendering the structure of the biofilm more compact and stable. 15,17 Hence, a combination of chemical and physical contributions, that is, hydrophobic molecules and surface roughness features (the latter of which are established by a complex combination of different biofilm matrix components), gives rise to the highly efficient wetting resistance of those biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…31,[33][34][35][36] However, only recently direct correlations between the biolm matrix composition and specic biolm properties could be determined. 31,34,35,37 Importantly, it was shown that the surface layer protein BslA is important for the surface stiffness and surface roughness 31 of NCIB 3610 biolms, and this protein also strongly affects the biolm wettability. 29,33,38 Both for B. subtilis B-1 bio-lms and biolms generated by Pseudomonas aeruginosa 39 it was shown that multi-valent ions protect the biolms from erosion.…”
Section: Introductionmentioning
confidence: 99%